Management of Differentiated Thyroid Cancer - Mancino, Anne T.; Kim, Lawrence T. (Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive, state-of-the art review of this field, and serves as a valuable resource for clinicians, surgeons and researchers with an interest in thyroid cancer. The book reviews new data about molecular genetics and molecular diagnostic approaches, covers diagnosis and treatment of localized disease, and conventional and newer therapies for dealing with recurrent and metastatic disease. Areas of controversy, with expert opinions from both outlooks, are also covered. Management of Differentiated Thyroid Cancer serves as a very useful resource for physicians and researchers dealing with, and interested in, this challenging malignancy. It provides a concise yet comprehensive summary of the current status of the field that will help guide patient management and stimulate investigative efforts. All chapters are written by experts in their fields and include the most up-to-date scientific and clinical information.
Keywords: Medicine.; Endocrinology.; Surgical oncology.; elektronické knihy; electronic books